Quality control of Cotesia flavipes (Cameron) (Hymenoptera: Braconidae) from different Brazilian bio-factories - Veiga, Ana C.P. [UNESP]; Vacari, Alessandra M. [UNESP]; Volpe, Haroldo X.L. [UNESP]; de Laurentis, Valéria L. [UNESP]; De Bortoli, Sergio A. [UNESP] (Taylor & Francis, 2013)
The goal of this study was to evaluate the quality of Cotesia flavipes from different bio-factories as biological control agents. We evaluated biological characteristics of the parasitoids throughout their lifespan, and measured the body length and width, abdomen width, thorax width and width and length of the right forewing of female and male parasitoids. Our results showed that the number of males and pupal viability were similar among the bio-factories; the number of emerged females was greater in bio-factories I and II; the egg-pupa period and the pupal period were shorter in bio-factory IV; and a greater longevity was found in bio-factories II and III. Sex ratio (at approximately 60% females) was satisfactory (in terms of suitability for release) across all bio-factories. For morphometric measurements, the body, abdomen and wing widths were similar in males; however, thorax width was greater in the males from bio-factory I; bio-factory III produced females with the highest body length; bio-factory I produced females with the greatest abdomen width; bio-factories III and IV produced females with the greatest wing length. Among the bio-factories studied, bio-factory IV produced the best quality C. flavipes, with respect to the greatest number of parasitoids per pupal mass (a mean of 57% more parasitoids) in a satisfactory sex ratio, and with the shortest developmental time, which facilitates faster rearing in the laboratory. Studies such as this, which assess the quality of a mass-produced C. flavipes, are crucial for the continued use of this parasitoid in controlling Diatraea saccharalis in the field. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: biological control; mass rearing; parasitoid; sugarcane; biocontrol agent; body size; crop pest; developmental biology; experimental apparatus; longevity; morphometry; moth; rearing; sex ratio; sugar cane; viability; wasp; Brazil